Discourse and Communication Analysis of the Milošević-Tuđman Agreement: Implications for Bosnia and Herzegovina - Mirdin Zilić; Adem Olovčić (Društvene i Humanističke Studije)
The Karađorđevo meeting in March 1991 between Slobodan Milošević and Franjo Tuđman holds profound historical significance in the context of escalating tensions in the former Yugoslavia. This paper employs a communicology perspective to comprehensively analyze the agreement, unveiling intricate negotiation dynamics and implications for Bosnia and Herzegovina. Analyzing the Milošević-Tuđman Agreement through communicology reveals communication patterns, rhetorical strategies, and implicit messages. This framework clarifies how language shapes perceptions, influences decisions, and impacts political contexts. The analysis examines the Karađorđevo meeting’s context, outlining political developments and rising nationalism leading to the negotiations. Using primary sources, it considers various stakeholders’ arguments about the agreement’s existence and implications. Expert teams’ roles in discussing Bosnia’s partition and key individuals’ statements are scrutinized. Findings shed light on implicit messages, power dynamics, and nationalistic discourses. Results highlight the agreement’s immediate and long-term consequences on Bosnia and Herzegovina, including its role in the Bosnian War. Critiques, controversies, and alternative interpretations are addressed. In conclusion, this paper summarizes key findings, underscores contributions to scholarship, and suggests avenues for future research. Analyzing the Milošević-Tuđman Agreement through communicology deepens our understanding of complex negotiation dynamics during a critical period in Bosnia and Herzegovina’s history.